The Role of the German Police in Maintaining Internal Security from the Defeat of Germany in World War I until the Fall of the Weimer Republic from the Perspective of German Researchers – An Analytical Study - Al Haj Ali, Abdul Majeed Ibrahim (Jordan Journal for History and Archaeology, 2023)
This study examines the burden that Germany’s defeat in World War I had on the German police in two respects: first the police were directly affected by the Treaty of Versailles and second, the police suffered – indirectly – from the pressure of increased resistance to the peace treaty and they had to constantly suppress internal disturbances. Although this study did not describe in detail the very long and complex process of reorganizing the police force, it does show that the police force did not have enough time to build a tightly integrated police force, due to repeated reorganizations within short time frames. The German police apparatus failed not only as a guardian of internal order, but also failed to protect its interests as an institution. The most important studies of German researchers dealt with the construction of the German police force and the problems it faced in different aspects and periods of time, and did not address this subject in an integrated manner for the period between 1918 and 1933, and the opinions of German researchers varied in explaining many of the attitudes and events suffered by the German police in that period. The study relies on a historical analytical approach based on the investigating information from its primary sources, and analysing its content and classifying in relation to the subject matter of the study.